3,7-Diazabicyclo[3.3.1]nonanes and 1,3-diazaadamantanes containing monoterpenoid moieties as synthetic adaptogens: synthesis, ADMET predictions, and in vivo biological activity - Kotliarova, Anastasiia A.; Ponomarev, Konstantin Yu; Morozova, Ekaterina A.; Suslov, Evgeniy V.; Pavlova, Alla V.; Tolstikova, Tatyana G.; Volcho, Konstantin P.; Salakhutdinov, Nariman F. (Medicinal chemistry research, 2025)
Fatigue is a widespread issue that affects both mental and physical performance, yet effective treatments remain limited. This study focused on developing and evaluating new synthetic adaptogens—compounds designed to enhance endurance and reduce fatigue. We synthesized and tested derivatives of 3,7-diazabicyclo[3.3.1]nonanes (bispidine) and 1,3-diazaadamantanes, incorporating monoterpenoid fragments to improve their pharmacological properties. Using SwissADME and PreADMET tools, we predicted that most of these compounds would be well-absorbed in the gastrointestinal tract and capable of crossing the blood-brain barrier. Among them, compound 2 , a 1,3-diazaadamantane derivative, stood out for its strong antifatigue effects at 10 mg/kg in swimming and running endurance tests in in vivo experiments with mice, even outperforming the reference drug bromantane. Acute toxicity tests showed that this compound has a high safety margin, with an LD 50 value 237.5 times greater than its effective dose. Further analysis of structure-activity relationships revealed that monosubstituted 1,3-diazaadamantane derivatives had the most promising effects, suggesting that specific chemical modifications can enhance performance. These findings indicate that this new class of synthetic adaptogens could offer a safe and effective way to combat fatigue, making them strong candidates for further pharmacological research and potential therapeutic use.